Quantum Sensing of Insulator‐to‐Metal Transitions in a Mott Insulator. Issue 5 (26th March 2021) - McLaughlin, Nathan J.; Kalcheim, Yoav; Suceava, Albert; Wang, Hailong; Schuller, Ivan K.; Du, Chunhui Rita
Abstract: Nitrogen vacancy (NV) centers, optically active atomic defects in diamond, have attracted tremendous interest for quantum sensing, network, and computing applications due to their excellent quantum coherence and remarkable versatility in a real, ambient environment. Taking advantage of these strengths, this paper reports on NV‐based local sensing of the electrically driven insulator‐to‐metal transition (IMT) in a proximal Mott insulator. The resistive switching properties of both pristine and ion‐irradiated VO2 thin film devices are studied by performing optically detected NV electron spin resonance measurements. These measurements probe the local temperature and magnetic field in electrically biased VO2 devices, which are in agreement with the global transport measurement results. In pristine devices, the electrically driven IMT proceeds through Joule heating up to the transition temperature while in ion‐irradiated devices, the transition occurs nonthermally, well below the transition temperature. The results provide direct evidence for nonthermal electrically induced IMT in a Mott insulator, highlighting the significant opportunities offered by NV quantum sensors in exploring nanoscale thermal and electrical behaviors in Mott materials. Abstract : The insulator‐to‐metal phase transition of archetypal Mott material VO2 is explored using nitrogen vacancy (NV) centers in diamond. Local temperature measurements are made across a voltage‐induced transition for pristine and doped VO2 . A nonthermal phase transition is observed in the doped samples, highlighting the significant opportunities offered by NV centers in exploring nanoscale thermal and electrical behaviors in Mott materials.